Ecofriendly Synthesis of Silver Nanoparticles Using Ananas comosus Fruit Peels: Anticancer and Antimicrobial Activities - Ayşe Baran; Cumali Keskin; Mehmet Fırat Baran; Irada Huseynova; Rovshan Khalilov; Aziz Eftekhari; Sevgi Irtegun-Kandemir; Deniz Evrim Kavak (Bioinorganic Chemistry and Applications, 2021)
Metallic nanoparticles are valuable materials and have a range of uses. Nanoparticles synthesized from plant wastes by environment-friendly methods have attracted the attention of researchers in recent years. Also, the advantages of biological resources and synthesis methods are attracting attention. In this study, silver nanoparticles were synthesized from Ananas comosus fruit peels using ecofriendly method steps. The characterization of the particles obtained was determined by using a UV-visible spectrophotometer (UV-Vis.), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction diffractometer (XRD), Fourier scanning electron microscope (FESEM), and transmission electron microscopy (TEM). The nanoparticles showed maximum absorbance at 463 nm, measuring 11.61 in crystal nanosize, and presented spherical in appearance. An antimicrobial activity test was determined with the minimum inhibition concentration (MIC) method. The nanoparticles showed promising inhibitory activity on the Gram-positive and Gram-negative pathogen microorganisms (Escherichia coli ATCC25922, Staphylococcus aureus ATCC29213, Bacillus subtilis ATCC11774, Pseudomonas aeruginosa ATCC27833 bacteria, and Candida albicans yeast) at low concentrations. The cytotoxic and growth inhibitory effects of silver nanoparticles on different cancer cell lines were examined via the MTT assay.